A critical discourse analysis of the representation of Boko Haram in Nigerian Presidential speeches - Duro-Bello, Olaoluwa (2022)
This thesis presents a critical analysis of the representation of Boko Haram and other key social actors in Nigerian political discourse. Much of the scholarly attention on Boko Haram’s representation in discourse has been focused on media sources (Ayoola and Olaosun, 2014; Chiluwa, 2016; Demarest, Godefroidt and Langer 2020; Hamid and Baba, 2014; Osisanwo, 2016; Ugwuona, 2015), while equally significant and dominant framing of the group in political discourse has been largely unexamined. To fill this void, this study analyses 28 speeches delivered by President Goodluck Jonathan between 2010 and 2015, a period that the Global Terrorism Index (2016) regards as the deadliest phase of Boko Haram terrorism. The study identifies and critically examines President Goodluck Jonathan’s discursive choices and the roles and relations he assigns to Boko Haram and other key social actors (the Government, Nigerians, the Security Forces, and himself) in the discourse. For qualitative analysis, the study draws on Norman Fairclough’s approach to critical discourse analysis, Theo van Leeuwen’s social actor network theory, and Michael Halliday’s systemic functional linguistics theory, while the quantitative analysis applies automated corpus analytical tools. Combining these broad strands of research methods triangulates the study such that the findings are not limited to isolated lexicalisations and representations within each speech but cumulatively explore the representation patterns across the entire corpus. In particular, the qualitative parsing of the texts informs the quantitative data from which conclusions are drawn about the frequencies, associations and patterns of representation across the corpus. The study’s findings reveal a polarised representation of in-group and out-group social actors, the construction and reinforcement of national identity, heightened assessment of terrorist threats, and the legitimisation of social action. Specifically, the study contributes to public understanding of Boko Haram’s portrayal in Nigerian political discourse. More generally, the study contributes to counter-terrorism discourse studies by unravelling the implicit processes by which social actors and social action in political discourse are enacted, normalised and legitimised.